Come organi coscienti. Per una teoria delle macchine a partire da Marx - De Stefano, Lorenzo (Bollettino Filosofico, 2025)
This article offers a reinterpretation of Marx’s theory of machines by grounding it in a zoo-techno-logical anthropology. It argues that Marx conceives the human being as a technical animal whose praxis mediates the relation between nature and society. Drawing on the Grundrisse and Capital, the study explores how machines embody social relations and scientific knowledge, becoming instruments of alienation under capitalism. Yet, their teleological structure also carries an emancipatory potential. The paper reframes debates on technological determinism and highlights the critical power of Marx’s thought in confronting digital capitalism and AI. Keywords: Anthropology, Capital, Machine Theory, Marx, Technology